Policy-Relevant Research: When Does It Matter? - Franklin, Gary M. (The American Society for Experimental NeuroTherapeutics, Inc., 2004)
Summary: Evidence-based medicine is most meaningful to policy makers when research questions are clearly informed by strategic health policy questions. In Washington State workers’ compensation, key structural characteristics allow for the conduct of effective policy-relevant research. These include clear authority and a stable funding stream, a formal relationship between a policy agency and a University, development of appropriate research capacity, development of research questions related to strategic goals, and a robust data source. The research conducted relies on computerized medical bills and work disability records, medical records, structured telephone surveys to collect data on pain, functional status, quality of life, and computerized data on employment status. The types of policy-relevant research include identification of factors leading to preventable disability, outcomes research of specific procedures, technology assessment, and “real-time” research that addresses rapidly emerging questions. Health policy changes implemented from research have been substantial in Washington State workers’ compensation, including: 1) noncoverage or partial coverage decisions for emerging technologies not proven to be of value to injured workers, 2) formal treatment guidelines and utilization review criteria for invasive, expensive, or marginally effective procedures, 3) disability prevention efforts, and 4) relatively rapid changes in policy as emerging patterns suggest harmful outcomes from existing treatments (e.g., schedule II opioids). Key structural characteristics must be in place to conduct policy-relevant research effectively. The workers’ compensation system in Washington State is a single-payer system with other unique properties that have allowed the emergence of these structural characteristics and the conduct of research linked to the strategic goals of policy makers.